PROSPECTIVE COMPONENTS FOR PUBLIC MECHANISMS TO COUNTERACT THE SOCIO-ECONOMIC CRISIS IN UKRAINE - Bielai S.V. (Pressing Problems of Public Administration, 2015)
The correlation of components for the complex public mechanism of counteraction the socio-economic crisis is defined. Pointed the prospective task of of using and implementing the state programs, social dialogue, plebsologi approach, monitoring, and the establishment of anticrisis situation centers as a prospestive component of public mechanisms to counter the socioeconomic crisis.